FEASIBILITY STUDY JOURNAL OF ROBUSTA GROUND COFFEE BUSINES IN TANGGAMUS REGENCY - Dwi Diana Sukmasari; Irmayani Noer; Ahfandi Ahmad (Gunung Djati Conference Series, 2026)
Tanggamus Regency is one of the main producers of Robusta coffee in Lampung Province; however,the added value enjoyed by farmers is still limited to the sale of raw coffee beans (green beans). This study aims to analyze the business feasibility of establishing a Robusta ground coffee processing unit to increase the economic value of local commodities and community economic empowerment. The research method used is descriptive quantitative by evaluating five main aspects of business feasibility: market and marketing aspects,technical and production aspects,human resource management aspects,legal aspect,and financial aspects. Data were obtained through field observations,interviews with stakeholders, and trend analysis of the contemporary coffee market. The results of the analysis indicate that from the market aspect,the demand for locally processed coffee continues to increase in line with the lifestyle trends of quality coffee consumption. From the technical aspect,the abundant availability of raw materials in Tanggamus ensures production sustainability. Analysis of the financial aspect using indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Net Benefit /Cost Ratio shows that this business has positive profit prospects and is feasible to implement. Coffee is a leading commodity for farmers in Lampung and its surroundings (South Sumatra and Bengkulu ). In 2019,the coffee production share of these three provinces reached 49 % of the national productions (BPS Lampung Province,2020). Robusta coffee is the largest agricultural crop in Indonesia produced in Lampung province, with an are of 162,954 hectares and production reaching 131,501 tons, with an average production capacity of 965 kg /ha. This study concludes that the development of the Robusta ground coffee industry in Tanggamus Regency is not only financially feasible but also strategic. In creating new job opportunities and strengthening the branding of regional coffee in the national market.